Identification of Salmonella enterica genes that influence plant host association - Engel, Tyler (My University, 2017)
Human enteric pathogens, such as Salmonella enterica, spend a significant portion of their life cycle associated with plant hosts. However, the specific genes required for S. enterica plant colonization have only begun to be examined. The goal of this study was to rapidly identify genes not previously known to influence S. enterica colonization of plants. To do so, a mutant library containing 40,000 unique transposon insertions was used to screen the entire S. enterica genome for fitness in germinating alfalfa sprouts over time. Transposon insertion sequence analysis revealed a number of genes related to metabolism, amino acid biosynthesis, virulence, transcriptional regulation, hypothetical and putative proteins, and non-coding intergenic regions that are required for S. enterica colonization of plants over time. The results of this study put us closer to creating novel strategies that prevent human enteric pathogens from colonizing fresh produce, leading to an overall improvement in food safety.